RELATIONSHIP BETWEEN DURATION OF KAMEKO CONSUMPTION (AREN FERMENTATION BEVERAGE) TO HEMATOLOGY LEVELS IN LABAHA VILLAGE, KECAMATAN WATOPUTE, MUNA DISTRICT, SOUTHEATS SULAWESI - Lio, Tiara Mayang Pratiwi Lio (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2019)
Aren (Arengapinnata) is a type of coconut palm which is one of the plants that can produce a type of traditional alcoholic beverage and has 4% alcohol content. Consumption of too much alcohol can cause anemia by affecting the process of blood formation (hematopoiesis) through metabolic and nutritional effects and also directly inhibits the proliferation of all cellular elements in the bone marrow. The purpose of this study was to determine the relationship of the duration of kameko consumption to hematological levels in Labaha Village, WatoputeSubdistrict, Muna Regency in 2018. This study is an observational analytical study with a cross sectional study design. The results showed that of the 25 respondents, the cross tabulation test showed, for the duration of consumption with hematological levels ? 5 years with a total of 17 respondents obtained abnormal examination scores for Hemoglobin levels (58.8%), Erythrocytes (41.2%), and Leukocytes (41.2%). While consumption of kameko> 5 years with a total of 8 respondents, abnormal hematological levels were obtained. While the spearman correlation test between the duration of consumption and the three parameters of Hemoglobin test, Erythrocyte and Leukocyte obtained sig. p <0.05 with correlation strength of each value r = - 0.953, r = - 0.934, r = 0.82. The conclusion of this study is that there is a correlation between the duration of consumption to hematological levels (Hemoglobin, Leukocytes and Erythrocytes) with Kameko consumption in Labaha Village, Watopute District, Muna Regency in 2018.